The European Union and diabetes: Why should diabetes stakeholders, like FEND and the International Diabetes Federation – European Region, think it necessary to spend time and effort in trying to influence the European Union? - Hall, M (International Diabetes Nursing, 2005)
Abstract In Europe, as in the rest of the world, diabetes is increasing rapidly. The International Diabetes Federation – European Region, FEND and other diabetes stakeholders are seeking to influence national governments and the European Union to action which would help in the prevention, diagnosis and control of diabetes. This article describes what is being done and how individual diabetes nurses can help in the campaign.